Relationships between Isometric Force-Time Characteristics and Dynamic Performance - Thomas Dos’Santos; Christopher Thomas; Paul Comfort; John J. McMahon; Paul A. Jones (Sports, 2017)
The purpose of this study was to explore the relationships between isometric mid-thigh pull (IMTP) force-time characteristics (peak force and time-specific force vales (100–250 ms)) and dynamic performance and compare dynamic performance between stronger and weaker athletes. Forty-three athletes from different sports (rowing, soccer, bicycle motocross, and hockey) performed three trials of the squat jump (SJ), countermovement jump (CMJ), and IMTP, and performed a one repetition maximum power clean (PC). Reactive strength index modified (RSImod) was also calculated from the CMJ. Statistically significant large correlations between IMTP force-time characteristics and PC (ρ = 0.569–0.674, p < 0.001), and moderate correlations between IMTP force-time characteristics (excluding force at 100 ms) and RSImod (ρ = 0.389–0.449, p = 0.013–0.050) were observed. Only force at 250 ms demonstrated a statistically significant moderate correlation with CMJ height (ρ = 0.346, p = 0.016) and no statistically significant associations were observed between IMTP force-time characteristics and SJ height. Stronger athletes (top 10) demonstrated statistically significantly greater CMJ heights, RSImods, and PCs (p ≤ 0.004, g = 1.32–1.89) compared to weaker (bottom 10) athletes, but no differences in SJ height were observed (p = 0.871, g = 0.06). These findings highlight that the ability to apply rapidly high levels of force in short time intervals is integral for PC, CMJ height, and reactive strength.